1976
DOI: 10.1042/bj1540049
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the activities of the enzymes of hepatic fatty acid oxidation during development of the rat

Abstract: 1. Changes in the activities of several enzymes involved in mitochondrial fatty acid oxidation were measured in the livers of developing rats between late foetal life and maturity. The enzymes studied are medium-and long-chain ATP-dependent acyl-CoA synthetases of the outer mitochondrial membrane and matrix, GTP-dependent acyl-CoA synthetase, camitine acyltransferase, enoyl-CoA hydratase, 3-hydroxyacyl-CoA dehydrogenase, general 3-oxoacyl-CoA thiolase and acetoacetyl-CoA thiolase. Developmental changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

1978
1978
2001
2001

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 39 publications
4
23
0
1
Order By: Relevance
“…Ketogenesis is also associated with increased substrate availability and changes in the activities of enzymes central to β-oxidation. Perinatal and dietary responses of rat hepatic mitochondrial HMG-CoA synthase coincide with changes in the expression and activity of liver carnitine palmitoyl transferase I (CPT-I) [6,[12][13][14][15], which suggests common regulatory mechanisms for these genes.…”
Section: Gene Expression Of Mitochondrial 3-hydroxy-3-methylglutaryl-mentioning
confidence: 99%
“…Ketogenesis is also associated with increased substrate availability and changes in the activities of enzymes central to β-oxidation. Perinatal and dietary responses of rat hepatic mitochondrial HMG-CoA synthase coincide with changes in the expression and activity of liver carnitine palmitoyl transferase I (CPT-I) [6,[12][13][14][15], which suggests common regulatory mechanisms for these genes.…”
Section: Gene Expression Of Mitochondrial 3-hydroxy-3-methylglutaryl-mentioning
confidence: 99%
“…After birth, apart from an increased delivery of non-esterified fatty acids to. the liver, there is an increase in the activity of the enzymes concerned with fl-oxidation in the liver, and particularly in the activity of the carnitine acyltransferase system (Augenfeld & Fritz, 1970;Foster & Bailey, 1976b). Carnitine also increases in concentration in liver after birth and it has been suggested that this is an important factor in the regulation of fatty acid oxidation and ketogenesis at this time (Robles-Valdes et al, 1976).…”
Section: Vol 176mentioning
confidence: 99%
“…Ketone bodies are then released into the blood and carried to the extrahepatic tissues where they are utilized (Robinson and Williamson, 1980 ;Williamson, 19821. In the fetal rat liver, NEFA oxidative capacity is low ; it increases during the first 12 hrs after birth, remains high during the suckling period to decrease at weaning (Sly and Walker, 1978 ; Benito, Whitelaw and Williamson, 1979 ;Ferré et al, 1983 ;Decaux et al, 1985). Changes in the liver capacity to oxidize NEFA are paralleled by changes in the activity of the mitochondrial enzymes of Boxidation and ketone body synthesis (Foster and Bailey, 1976b ;ling, together with the high availability of NEFA in the plasma lead to high ketonebody blood concentrations which decrease after weaning (Lockwood and Bailey, 1971 ;Foster and Bailey, 1976a (Bougneres et al, 1986). Moreover, for a similar blood concentration, ketone-body utilization is 2-fold higher than in the adult.…”
Section: Introductionmentioning
confidence: 99%